2012
DOI: 10.1007/s00247-012-2352-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antenatal growth and prematurity on brain white matter: diffusion tensor study

Abstract: Children with low birth weight relative to gestational age show delay and/or anomaly in white matter maturation at term-equivalent age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Indeed, most of this research demonstrates that FA and diffusion variations in the CC correlate significantly with gestational age [36] , [38] , [47] , although some found an association with birth weight instead of gestational age [48] . Nevertheless, extreme prematurity and extremely low birth weights imply multiple complications that could influence brain development and may not be applicable to healthy term infants.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, most of this research demonstrates that FA and diffusion variations in the CC correlate significantly with gestational age [36] , [38] , [47] , although some found an association with birth weight instead of gestational age [48] . Nevertheless, extreme prematurity and extremely low birth weights imply multiple complications that could influence brain development and may not be applicable to healthy term infants.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have reported significant associations of birth weight with FA and MD in preterm infants at term‐equivalent ages (Lepomäki et al, ). In this study, with respect to full‐term neonates, both birth weight and crown‐heel length positively correlated with FA and negatively correlated with MD, AD, and RD, indicating more advanced WM maturation.…”
Section: Discussionmentioning
confidence: 95%
“…Ghods et al [19] demonstrated a positive correlation between head circumference growth and neurodevelopmental outcome. Normal antenatal growth is associated with more mature WM and reduced MD is seen with improved postnatal development and maturation [20]. All observed effects were in the hypothesized direction, suggesting improved maturation of the cerebral connective tracts among infants receiving enhanced nutrition.…”
Section: Discussionmentioning
confidence: 99%